2013
DOI: 10.1074/jbc.m112.424515
|View full text |Cite
|
Sign up to set email alerts
|

The Trithorax Group Protein Ash2l Is Essential for Pluripotency and Maintaining Open Chromatin in Embryonic Stem Cells

Abstract: Background:The trithorax protein Ash2l is a core component of the MLL complex essential for H3K4 methylation and mouse embryonic development. Results: Ash2l depletion promotes differentiation and chromatin compaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 66 publications
6
52
1
Order By: Relevance
“…S3). In contrast to a recent report on Ash2l in ESCs (Wan et al, 2013), ~10,000 TSS promoters enriched for Ash2l were observed. These strongly correlated with Mll2 sites (88%) and CpG islands (84%), indicating that Ash2l was also localised at most Mll2-occupied TSSs.…”
Section: Characterisation Of Mll2 Binding Sites In the Esc Genomecontrasting
confidence: 49%
“…S3). In contrast to a recent report on Ash2l in ESCs (Wan et al, 2013), ~10,000 TSS promoters enriched for Ash2l were observed. These strongly correlated with Mll2 sites (88%) and CpG islands (84%), indicating that Ash2l was also localised at most Mll2-occupied TSSs.…”
Section: Characterisation Of Mll2 Binding Sites In the Esc Genomecontrasting
confidence: 49%
“…Importantly, we demonstrated a novel endogenous interaction between UTX and RAR and determined that this confers target gene specificity and gives a physiological significance to the physical association between the H3K27 demethylase UTX and the MLL3/4-containing H3K4 methyltransferase complexes in the regulation of gene expression, as previously reported (1,2). In particular, the trithorax protein ASH2L is considered one of the core subunits of all known H3K4-specific MLL/SET methyltransferase complexes (15), functions as an oncoprotein that is overexpressed in human tumors (27), and is essential for pluripotency in ES cells (28). NCoA6, which is essential for nuclear receptor function in vivo, is amplified and overexpressed in various human cancers (29).…”
Section: Discussionmentioning
confidence: 96%
“…Genome-wide assessment of Wdr5 and Oct4 indicated that they cooccupy a subset of gene promoters together with Rbbp5, Sox2, and Nanog, providing a possible molecular mechanism by which Wdr5 is necessary for ESC self-renewal (124). Depletion of Ash2l also downregulates the expression of several pluripotency factors, concomitant with the upregulation of differentiation-associated genes of all three germ layers, resulting in a loss of ESC self-renewal (126).…”
Section: Set1a/b and Mll Complexes In Escsmentioning
confidence: 99%